Nekateri ustavnopravni vidiki pooblastil Urada za varstvo konkurence - Keresteš, Tomaž; Repas, Martina (LeXonomica, 2012)
Some Constitutional Aspects of Investigation Powers of the Slovenian Competition Office. This contribution deals with the conformity of investigation powers of the Competition Office with the provisions of Slovenian Constitution. Authors in first place analyze the conformity of powers with the right for protection of home and protection of private correspondence. In case of protection of home they argue on the basis of ECHR and German constitutional case law that the notion of home can cover business premise, especially in cases of limited public access. Regarding the right for protection private correspondence they also call attention to the fact that the notion private correspondence covers also private correspondence of employees at work and that the protection of this right in the Slovenian Constitution is extremely strict. Nekateri ustavnopravni vidiki pooblastil Urada za varstvo konkurence. Prispevek obravnava skladnost preiskovalnih pooblastil Urada za varstvo konkurence z določbami Ustave Republike Slovenije. Avtorja predvsem analizirata skladnost pooblastil s pravico do nedotakljivosti stanovanja in pravico do komunikacijske zasebnosti. V primeru nedotakljivosti stanovanja na temelju določb EKČP in nemške ustavnosodne prakse zagovarjata stališče, da pojem stanovanja in drugih prostorov lahko zajema tudi poslovne prostore, še posebej, če zanje velja omejen dostop javnosti. Glede pravice dokomunikacijske zasebnosti pa opozarjata, da komunikacijska zasebnost zajema tudi zasebno komunikacijo zaposlenega na delovnem mestu in da je zaščita te pravice v Ustavi Republike Slovenije izjemno stroga.